Demographic, clinical and language characteristics of Malaysian patients with aphasia: a retrospective study - Aziz MAA,; Razak AR,; Farid AHM,; Hamid BA,; Taha NA,; Garraffa M,; Alisaputri ML, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Limited research has been conducted in Malaysia on the characteristics of patients with aphasia. To address this gap, a retrospective study was conducted at Hospital Rehabilitasi Cheras (HRC). The study aimed to profile the demographic, clinical, and language characteristics of patients who underwent speech therapy for aphasia. Medical records from 2014 to 2017 were reviewed, focusing on 1,259 adult patients who were referred to the Speech Therapy Unit. Analysis included demographics, clinical aspects, and linguistic features. The Western Battery of Aphasia-Revised (WAB-R), a comprehensive assessment tool, was used to evaluate the language abilities. Among the patients' files analysed, a total of 211 contained WAB-R test results. The demographic profile revealed a higher proportion of male patients compared to females, with Malay patients comprising the majority, followed by Chinese and Indians. Age distribution included 41.7% older adults (aged 55 and above), 37.9% middle-aged (aged 36-55), and 20.4% younger adults (aged 18-35). Notably, 44.5% had completed high school education. Clinically, right- sided hemiparesis was prevalent as noted with 67.8% of patients, while 14.7% had left-sided hemiparesis. The primary cause of aphasia was stroke, accounting for 71.1% of cases, with ischemic stroke being the dominant subtype (56.9%). Fluent aphasia was presented in 50.2% of the cases, compared to 49.3% of non-fluent aphasia. Anomic aphasia was the most common subtype (35.5%), followed by global aphasia (27.5%) and Broca’s aphasia (17.5%). The language profile provided a detailed description, encompassing linguistic aspects relevant to different aphasia types. These preliminary findings yielded valuable insights and hold significant implications for the clinical management of aphasia patients in Malaysia.